The theological centre of Pauline theology as it relates to the Holy Spirit - Pretorius, Mark (HTS teologiese studies, 2006)
The issue as to what constitutes the “heart of Pauline theology” is a contentious one in academic debates. The traditional view is the one fostered by the Reformers and perpetuated by generations of Protestants namely that “justification by faith” is the key to Paul’s theology. Unfortunately, upon careful reading of Paul’s letters, the inadequacy of such a view becomes apparent as such a focus would fail to cast the net broadly enough to capture all of Paul’s theological concerns. In saying this and without denying the presence of other determining factors, especially Christology and eschatology, shape the framework of Paul’s pneumatology. There is no doubt that in their eschatological significance, the death and resurrection of Christ control Paul’s teaching on the work of the Spirit within the lives of believers. It could then be argued that as part of the fundamental core of Paul’s understanding of the Gospel, the Spirit is rather close to the centre of things.